(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Obesity is one of the most frequently found health risks with increasing in its prevalence all over the world. Several measures of obesity like body mass index, waist circumference and percent of body fat had been used in many studies as predictor of pulmonary function tests. Objectives:To evaluate the effect of anthropometric measurements on pulmonary function tests, and explore the association between body fat percent and pulmonary function tests. Methods: A total of one hundred subjects were recruited from both sexes (fifty with normal and fifty with high body mass index). Body mass index, waist circumference and percent of body fat were measured for each subject. Results:This study shows a significant reduction in spirometric parameters (except for FEV1/FVC ratio) in high body mass index groups compared to those with normal body mass index in both sexes, with a significant negative correlation between percent of body fat and waist circumference with spirometric parameters in high body mass index groups had been identified. Conclusion:Obesity has a restrictive rather than obstructive pattern of lung impairment. Excess body fat and abdominal obesity have anadverse affect on lung function. Keywords:Pulmonary function test, BMI, WC, BF%